2019
DOI: 10.1080/21505594.2019.1589362
|View full text |Cite
|
Sign up to set email alerts
|

Homophilic protein interactions facilitate bacterial aggregation and IgG-dependent complex formation by theStreptococcus canisM protein SCM

Abstract: Streptococcus canis is a zoonotic agent that causes serious invasive diseases in domestic animals and humans, but knowledge about its pathogenic potential and underlying virulence mechanisms is limited. Here, we report on the ability of certain S. canis isolates to form large bacterial aggregates when grown in liquid broth. Bacterial aggregation was attributed to the presence and the self-binding activity of SCM, the M protein of S. canis, as evaluated by bacterial sedimentation assays, immunofluorescence-and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 46 publications
(80 reference statements)
1
10
0
Order By: Relevance
“…The M-protein is a well-characterized virulence factor of S. pyogenes , and the orthologous nature of the SCM protein suggests a potential for a similar role in S. canis pathogenesis. To investigate the role of SCM in S. canis virulence, we utilized a SCM insertional mutant made from the S. canis G361 clinical isolate strain that no longer produces the SCM protein and exhibits reduced aggregate formation in culture [ 32 ]. We confirmed that loss of SCM did not alter in vitro growth of S. canis compared to wildtype S. canis in bacteriologic media (THB, Figure 1 A) or tissue culture media (RPMI-1640, Figure 1 B).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The M-protein is a well-characterized virulence factor of S. pyogenes , and the orthologous nature of the SCM protein suggests a potential for a similar role in S. canis pathogenesis. To investigate the role of SCM in S. canis virulence, we utilized a SCM insertional mutant made from the S. canis G361 clinical isolate strain that no longer produces the SCM protein and exhibits reduced aggregate formation in culture [ 32 ]. We confirmed that loss of SCM did not alter in vitro growth of S. canis compared to wildtype S. canis in bacteriologic media (THB, Figure 1 A) or tissue culture media (RPMI-1640, Figure 1 B).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, loss of SCM in S. canis possibly reduces surface proteins with greater hydrophobicity, leading to the observed decrease in biofilm formation. Alternatively, because SCM activity is associated with S. canis aggregation microcolony formation in vitro [ 56 ], loss of homophilic interactions between SCM in the Δ scm strain may alter the morphology of S. canis biofilms [ 32 , 57 ]. In fact, although there was no difference in the relative fluorescent units (RFU) of WT G361 and Δ scm biofilms in RPMI-1640, the morphology of the biofilms was visibly different.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations